Odpowiedź:
zad. 1 odpowiedź A
zad. 2 odpowiedź C
zad. 3 odpowiedź A
Szczegółowe wyjaśnienie:
zad. 1
[tex]A = -2[/tex]
[tex]B= -4\frac{1}{3} = -4,(3)[/tex]
[tex]C = -\frac{13}{2} = -6\frac{1}{2} = -6,5[/tex]
[tex]D = -4\frac{2}{3} = -4,(6)[/tex]
zad. 2
A)
[tex]\frac{-3 * \sqrt{25} }{\sqrt[3]{64} } = \frac{-3 *5 }{ 4 } = \frac{-15}{4} = -3 \frac{3}{4}[/tex]
B)
[tex]-\sqrt{5} + \sqrt{5} = 0[/tex]
C)
[tex]\frac{\sqrt{3} }{2}[/tex] Liczba [tex]\sqrt{3}[/tex] jest niewymierna więc całe działanie jest niewymierne
D)
[tex]2\frac{1}{2} = 2,5[/tex]
zad. 3
[tex]4\frac{1}{2} + 3,8 = 4,5 + 3,8 = 8,3[/tex]